2021
DOI: 10.7717/peerj.10524
|View full text |Cite
|
Sign up to set email alerts
|

A heat-shock 20 protein isolated from watermelon (ClHSP22.8) negatively regulates the response of Arabidopsis to salt stress via multiple signaling pathways

Abstract: Heat-shock protein 20s (HSP20) were initially shown to play a role during heat shock stress; however, recent data indicated that HSP20 proteins are also involved in abiotic stress in plants. Watermelon is known to be vulnerable to various stressors; however, HSP20 proteins have yet to be investigated and characterized in the watermelon. In a previous study, we identified a negative regulator of salt stress response from watermelon: ClHSP22.8, a member of the HSP20 family. Quantitative real-time PCR (qRT-PCR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For example, the overexpression of AtHSP90.2 , AtHSP90.5 , and AtHSP90.7 reportedly increases the sensitivity of Arabidopsis to salt and drought conditions [ 44 ]. Earlier research confirmed that plant SHSP20s modulate the resistance to various abiotic stresses (e.g., heat, drought, and cold) and also influence somatic embryogenesis and seed germination [ 45 , 46 , 47 ]. In the present study, HSP90 and two SHSPs (HSP20s) were up-regulated in response to LK stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the overexpression of AtHSP90.2 , AtHSP90.5 , and AtHSP90.7 reportedly increases the sensitivity of Arabidopsis to salt and drought conditions [ 44 ]. Earlier research confirmed that plant SHSP20s modulate the resistance to various abiotic stresses (e.g., heat, drought, and cold) and also influence somatic embryogenesis and seed germination [ 45 , 46 , 47 ]. In the present study, HSP90 and two SHSPs (HSP20s) were up-regulated in response to LK stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of the CaHSP18.1a decreased at higher NaCl and mannitol concentrations. The response pattern of CaHSP18.1a that rapidly and sharply responded to salt and drought stress in a short time, and then had slight variations, was similar to quite a few HSP20s such as TaHSP23.9 [53] and ClHSP22.8 [54]. Thus, CaHSP18.1a may play a role in pepper which rapidly adapts to drought and salt stress.…”
Section: Discussionmentioning
confidence: 81%
“…HSP20 is abundant in plants and the most produced protein under heat stress. It has been proven to be involved in plant response to biotic and abiotic stresses (Peffer et al, 2019;Wu et al, 2019;Ding et al, 2020;He et al, 2021). In Arabidopsis, HSP17.4 was highly expressed after infection by Pseudomonas syringae (Sewelam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%